Child health and unhealthy sanitary practices in India: Evidence from Recent Round of National Family Health Survey-IV() - Dwivedi, Laxmi Kant (SSM Popul Health, 2018)
OBJECTIVES: Despite threefold increase in investment (from Rs. 28,500 million to Rs. 90,000 million during 2014–17) in the allocation of funds for the Clean India movement, creating awareness and various social movements, more than half of the rural population (52.1%) of the country still defecates in the open. This study aims to examine the prevalence of improved sanitation facilities and safe stool disposal in India and its states. It also aims to further establish inter-linkages between safe stool disposal and child health. STUDY DESIGN: The present study uses data from the fourth round of the recently conducted cross-sectional National Family Health Survey (NFHS-4, 2015–16). METHODS: Two proxy indicators used to assess the effect on child health are: stunting and mortality of children under the age of five years. Multivariate logistic regression analysis was employed to examine the impact of improved sanitation facilities and safe stool disposal on child health measured by height-for-age as a dichotomous variable. Multivariate discrete-time logistic model was used to examine the impact of improved sanitation facilities and safe stool disposal on under-five child deaths. RESULTS: The results reveal that unsafe disposal of stools are one of the main contributing factors responsible for stunting and under-five mortality among children. The prevalence was clearly seen to be higher in households where open defecation and unsafe stool disposal were practised. CONCLUSIONS: The central behavioural change to be brought about among the people is to improve the cleanliness levels of the neighbourhood and help children spend their childhood free from the misery of malnourishment or in the worst case, death. It is not an impossible task for a country that houses the cleanest village in Asia, Mawlynnong in the Northeast state of Meghalaya, India. If one state could do it, it could be replicated in other states too.